Occupation of Sambisa Forest and Boko Haram Insurgency in Northeastern Nigeria as Security Threat and Challenges to Sustainable Forest Management (Global Journal of Science Frontier Research, 2018)
Since 2013 when the Boko Haram insurgents found a safe haven in the Sambisa forest from where they launch their attacks on the Nigerian state, neither Nigeria nor the forest has known any peace ever since. Although the socioeconomic, socio-political and socio-cultural consequences of Boko Haram insurgency have been highlighted by many writers and researchers, nothing is yet known regarding its consequences on the Sambisa forest itself. With experiences from other parts of the globe, this paper highlights the factors linking forests with conflict. The first fact emerging from the research is that Nigeria is not the only country where conflicts have been linked with forests rather it is a common and worldwide phenomena, as countries experiencing violent conflict in their forests account for about 40 percent of the world's tropical forests. Among factors linking forests with conflicts include their remoteness, seclusion, inaccessibility and richness and hence the ability to provide refuge, funds and food for combatants. Among the negative consequences of such conflicts on forest is the likelihood of its destruction and or occupation by the state forces in an effort to prevent insurgent groups from continuing using it as a hideout to carry out their criminal activities. This happens to be the fate of the Sambisa forest today. Based on its location, wide expanse and abundant content of wood and non-wood resources, it was not surprising that the insurgents found its confines very alluring hence its occupation. With the recapture of the Sambisa forest by the Nigerian military, she decided to be holding her Small Arms Championship and other sporting events in the forest as a way of keeping it permanently safe from insurgents. The implication of this development is that the forest has lost its reserve status.